Pengaruh Kekerasasn Seksual Yang Difasilitasi Teknologi Terhadap Depresi Pada Wanita Dewasa Awal Pengguna Media Sosial - Mu'azzaroh, Amadea Aqsa; Yuniar Cahyanti, Ika (Jurnal Syntax Fusion, 2023)
This study aims to determine whether or not there is an effect of technology-facilitated sexual violence on depression in early adult women using social media. Technology-facilitated sexual violence is a series sexually aggressive or harmfully harassing behavior using communication technologies. Depression is a mood disorder characterized by feelings of sadness or loss of interest in activities for at least 2 weeks. This research was conducted on 150 female subjects aged 18-25 years who owned and used social media and had been victims of technology-facilitated sexual violence. The method used was a quantitative survey, in which participants were asked to fill out the Technology Facilitated Sexual Violence Scale and Beck Depression Inventory-II. The analysis used was multiple linear regression with the help of the statistical program IBM SPSS 25.00 for mac. The results showed that technology-facilitated sexual violence simultaneously plays a role of 36.5% of depression.